Sodium battery positive electrode material precursor with core-shell structure as well as preparation method and application of sodium battery positive electrode material precursor

By using a core-shell structure of Ni-based MOF material in the positive electrode material of sodium ion battery, combined with the multi-layer structure of Ni, Fe, Mn, Cu, Ti and Zr, the problems of stability and rate performance of nickel-ferromanganese materials are solved, and the problem of nickel-ferromanganese materials is achieved. It has a high capacity and low cost sodium ion battery cathode material, suitable for industrial production.

CN119133392APending Publication Date: 2024-12-13JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411239150.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The nickel-ferromanganese layered oxide positive electrode material has poor air stability, poor cycle stability and unsatisfactory rate performance. It is difficult for traditional coating methods to solve these problems, resulting in limited performance of sodium ion batteries.

Method used

The precursor of sodium electropositive material with core-shell structure, the core is a Ni-based MOF material with porous structure, the intermediate layer contains Ni, Fe and Mn, and the outer shell layer contains Mn, Cu, Ti and Zr. It is prepared by co-precipitation reaction to simplify production The process is suitable for large-scale industrial production.

Benefits of technology

The capacity, cycle stability and structural stability of the cathode material are improved, the preparation cost is reduced, and it is suitable for large-scale production, achieving high capacity and good electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133392A_ABST
    Figure CN119133392A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium battery positive electrode material precursor with a core-shell structure as well as a preparation method and application of the sodium battery positive electrode material precursor. The sodium battery positive electrode material precursor with the core-shell structure comprises an inner core, the surface of the inner core is coated with a middle layer, the surface of the middle layer is coated with a shell layer, the inner core is a Ni-based MOF material with doping elements, the middle layer comprises at least two of Ni, Fe and Mn, and the shell layer comprises at least one of Mn, Cu, Ti and Zr. According to the precursor, the Ni-based MOF material with a porous structure is used as an inner core, so that on one hand, relatively high capacity can be provided for the positive electrode material, and on the other hand, sodium ions can enter more favorably when the positive electrode material is prepared, and the power performance of the positive electrode material can be improved favorably; the middle layer not only has relatively low preparation cost, but also can provide certain capacity for the positive electrode material prepared from the middle layer; the shell layer can effectively improve the structural stability of the positive electrode material prepared from the shell layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and relates to a sodium-ion positive electrode material precursor with a core-shell structure and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are secondary batteries that rely on the movement of sodium ions between positive and negative electrodes to complete charging and discharging. Their working principle is similar to that of widely used lithium-ion batteries. Compared with lithium-ion batteries, sodium-ion batteries are cheaper and therefore have better application prospects.

[0003] The performance of sodium-ion batteries is mainly affected by the positive electrode material. Among them, layered oxide positive electrode materials have higher specific capacity and voltage advantages, and have inherent cost advantages, not only because such materials can learn from the highly mature solid phase method or coprecipitation method often used in lithium-ion batteries to achieve low-cost large-scale production, but also because of its rich selection of active elements. However, the main problems currently faced by nickel-iron-manganese layered oxide positive electrode materials are poor air stability, poor cycle stability, and unsatisfactory rate performance of the materials, which are difficult to solve by the traditional two-step coating method.

[0004] Therefore, providing a strategy to improve the stability of sodium ion battery cathode materials and ensure their good capacity is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a core-shell structured sodium cathode material precursor and a preparation method and application thereof.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a sodium-based positive electrode material precursor with a core-shell structure, the core-shell structure sodium-based positive electrode material precursor comprising an inner core, the surface of the inner core being coated with an intermediate layer, the surface of the intermediate layer being coated with an outer shell layer, the inner core being a Ni-based MOF material with doping elements, the intermediate layer comprising at least two of Ni, Fe and Mn, and the outer shell layer comprising at least one of Mn, Cu, Ti and Zr.

[0008] The precursor of the present invention uses a Ni-based MOF material with a porous structure as the core. The nickel-rich and porous properties can provide a higher capacity for the positive electrode material on the one hand, and on the other hand, it can be more conducive to the entry of sodium ions when preparing the positive electrode material, which is beneficial to improving the power performance of the positive electrode material; the middle layer not only has a lower preparation cost, but also can provide a certain capacity for the positive electrode material prepared by using it; the outer shell layer can effectively improve the structural stability of the positive electrode material prepared by using it.

[0009] The positive electrode material prepared by using the precursor provided by the present invention not only has a higher capacity and good cycle stability, but also can effectively reduce the preparation cost.

[0010] In one embodiment, the intermediate layer is a combination of Fe and Mn, which can ensure low preparation cost and enable the positive electrode material to have a certain capacity.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] Preferably, the doping element includes at least one of Cu, Al, Mg, Zr, Ti and Ca.

[0013] Preferably, based on the total mass of the sodium electric positive electrode material precursor of the core-shell structure, the doping amount of the doping element is 800-2500ppm, for example, it can be 800ppm, 850ppm, 900ppm, 950ppm, 1000ppm, 1050ppm, 1100ppm, 1150ppm, 1200ppm, 1250ppm, 1300ppm, 1350ppm, 1400ppm, 1450ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2150ppm, 2300ppm, 2400ppm or 2500ppm, etc.

[0014] Preferably, based on the total mass of the core-shell structured sodium-based cathode material precursor as 100%, the content of the inner core is 10-40%, for example, it can be 10%, 12%, 14%, 15%, 17%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32.5%, 35%, 38% or 40%, etc.

[0015] Preferably, based on the total mass of the core-shell structured sodium-based positive electrode material precursor as 100%, the content of the intermediate layer is 20-80%, for example, it can be 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32.5%, 35%, 38%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc.

[0016] Preferably, based on the total mass of the core-shell structured sodium cathode material precursor as 100%, the content of the outer shell layer is 10-40%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0017] In a second aspect, the present invention provides a method for preparing a core-shell structured sodium cathode material precursor as described in the first aspect, the preparation method comprising the following steps:

[0018] (1) providing a Ni-based MOF material having a doping element, and preparing a base liquid using the Ni-based MOF material having a doping element;

[0019] (2) adding a first metal salt solution, a precipitant solution and a complexing agent solution to the base solution in parallel to perform a coprecipitation reaction, wherein the metal element in the first metal salt solution is of the same type as the metal element in the intermediate layer, thereby obtaining an inner core coated with the intermediate layer;

[0020] (3) replacing the first metal salt solution with a second metal salt solution, wherein the metal element in the second metal salt solution is consistent with the type of the metal element in the outer shell layer, and continuing the coprecipitation reaction to obtain the core-shell structured sodium cathode material precursor.

[0021] The method of the invention is simple, simplifies the production process of the core-shell structure material, and is suitable for large-scale industrial production.

[0022] As a preferred technical solution of the method for preparing the core-shell structured sodium cathode material precursor of the present invention, the method for preparing the Ni-based MOF material with doping elements in step (1) comprises:

[0023] (a) mixing a reaction substrate, a catalyst and a solvent to obtain a solution A;

[0024] (b) dissolving nickel salt and M salt in a solvent, where M is a doping element, to obtain solution B;

[0025] (c) Solution A and solution B are mixed and reacted to obtain a Ni-based MOF material with doping elements.

[0026] Preferably, in step (a), the reaction matrix includes at least one of 2-methylimidazole, benzimidazole and bisbenzimidazole.

[0027] Preferably, the catalyst is selected from at least one of NH4OH and NaOH, preferably NH4OH.

[0028] Preferably, step (a) is: dissolving the reaction matrix in NH4OH solution to obtain solution A.

[0029] Preferably, the mass content of NH3 in the NH4OH solution is 25-40%, for example, it can be 25%, 27%, 30%, 32%, 34%, 36%, 38% or 40%, etc.

[0030] Preferably, in step (a), the concentration of 2-methylimidazole in the solution A is 1.9-3.8 mol / L, for example, it can be 1.90 mol / L, 2.1 mol / L, 2.3 mol / L, 2.5 mol / L, 2.7 mol / L, 3.0 mol / L, 3.2 mol / L, 3.4 mol / L, 3.6 mol / L or 3.8 mol / L, etc.

[0031] Preferably, the nickel salt in step (b) is at least one of nitrate, sulfate or chloride, preferably nitrate.

[0032] Preferably, the M salt in step (b) is at least one of nitrate, sulfate or chloride, preferably nitrate.

[0033] Preferably, in step (b), the concentration of the nickel salt in the solution B is 0.6-1.2 mol / L, for example, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 1.0 mol / L or 1.2 mol / L.

[0034] Preferably, in step (b), the concentration of the M salt in the solution B is 0.07-0.14 mol / L, for example, 0.07 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L or 0.14 mol / L.

[0035] Preferably, in step (c), the mixing and reacting process is carried out under stirring conditions.

[0036] Preferably, in step (c), the temperature of the mixing and reaction is 20-30°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C or 30°C.

[0037] Preferably, in step (c), the reaction time is 20-30 h, for example, it can be 20 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h or 30 h.

[0038] Preferably, in step (c), after the reaction, solid-liquid separation, solid washing, drying and grinding are further performed. The reagent used for washing can be deionized water or ultrapure water.

[0039] As a preferred technical solution for the preparation method of the core-shell structured sodium cathode material precursor of the present invention, in step (1), the concentration of the Ni-based MOF material with doping elements in the base liquid is 2-8 g / L, for example, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L or 8 g / L, etc.

[0040] Preferably, in step (1), the temperature of the base liquid is 20-80°C, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.

[0041] Preferably, in step (1), the concentration of aqueous ammonia in the base liquid is 0-10 g / L, for example, it can be 0 g / L, 0.05 g / L, 0.1 g / L, 0.3 g / L, 0.5 g / L, 0.8 g / L, 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L, etc. Wherein, the aqueous ammonia concentration in the base liquid of 0 g / L means that the base liquid does not contain aqueous ammonia, for example, water can be used as the base liquid.

[0042] Preferably, in step (1), the pH of the base solution is 8-12, for example, it can be 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12, etc.

[0043] Preferably, the concentration of the first metal salt solution in step (2) is 80-120 g / L, for example, it can be 80 g / L, 82 g / L, 85 g / L, 88 g / L, 90 g / L, 92 g / L, 93 g / L, 95 g / L, 98 g / L, 100 g / L, 105 g / L, 108 g / L, 110 g / L, 113 g / L, 116 g / L, 118 g / L or 120 g / L, etc.

[0044] Preferably, the feed rate of the first metal salt solution in step (2) is 1-10 L / h, for example, it can be 1 L / h, 2 L / h, 2.5 L / h, 3 L / h, 3.5 L / h, 4 L / h, 4.5 L / h, 5 L / h, 5.5 L / h, 6 L / h, 6.5 L / h, 7 L / h, 7.5 L / h, 8 L / h, 9 L / h or 10 L / h, etc.

[0045] Preferably, the mass concentration of the precipitant solution in step (2) is 10-30%, for example, it can be 10%, 12%, 15%, 18%, 20%, 22%, 24%, 25%, 27%, 28% or 30%, etc.

[0046] Preferably, the feed rate of the precipitant solution in step (2) is 1-7 L / h, for example, it can be 1 L / h, 1.5 L / h, 2 L / h, 2.5 L / h, 3 L / h, 3.5 L / h, 4 L / h, 4.5 L / h, 5 L / h, 5.5 L / h, 6 L / h, 6.5 L / h or 7 L / h, etc.

[0047] Preferably, the mass concentration of the complexing agent solution in step (2) is 10-20%, for example, it can be 10%, 12%, 14%, 15%, 17%, 18% or 20%.

[0048] Preferably, the feeding rate of the complexing agent solution in step (2) is 0.1-1 L / h, for example, it can be 0.1 L / h, 0.3 L / h, 0.5 L / h, 0.6 L / h, 0.7 L / h, 0.8 L / h or 1 L / h, etc.

[0049] Preferably, the temperature of the coprecipitation reaction in step (2) is 20-80°C, for example, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc.

[0050] Preferably, the coprecipitation reaction in step (2) is accompanied by stirring, and the stirring speed is 100-400 r / min, for example, it can be 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min or 400 r / min.

[0051] Preferably, the ammonia concentration in the system of the coprecipitation reaction in step (2) is 0-13 g / L, for example, it can be 0 g / L, 0.05 g / L, 0.1 g / L, 0.3 g / L, 0.5 g / L, 0.8 g / L, 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, 10 g / L, 10.5 g / L, 11 g / L, 11.5 g / L, 12 g / L, 12.5 g / L or 13 g / L, etc. Here, the ammonia concentration in the coprecipitation reaction system being 0 g / L means that the coprecipitation reaction system does not contain ammonia.

[0052] Preferably, in step (2), the pH of the coprecipitation reaction is 8-12.5, for example, it can be 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 or 12.5, etc.

[0053] Preferably, the particle size D50 of the core coated with the intermediate layer in step (2) is 10-12 μm, for example, it can be 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, etc.

[0054] In one embodiment, the coprecipitation reaction is carried out in a reactor, and the particle size is monitored during the reaction. Before the particle size reaches the requirement, a high-efficiency concentrator is used during the reaction to collect all the particles and return them to the reactor for continued reaction and growth. When the particle size reaches the preset particle size, the feed is stopped to complete step (2).

[0055] Preferably, the concentration of the second metal salt solution in step (3) is 80-120 g / L, for example, it can be 80 g / L, 85 g / L, 88 g / L, 90 g / L, 92 g / L, 95 g / L, 100 g / L, 103 g / L, 106 g / L, 108 g / L, 110 g / L, 115 g / L or 120 g / L, etc.

[0056] Preferably, the feed rate of the second metal salt solution in step (3) is 1-10 L / h, for example, it can be 1 L / h, 2 L / h, 3 L / h, 3.5 L / h, 4 L / h, 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h or 10 L / h, etc.

[0057] Preferably, the second metal salt in the second metal salt solution in step (3) is sulfate.

[0058] Preferably, the time for continuing the coprecipitation reaction in step (3) is 2-4 h, for example, it can be 2 h, 2.2 h, 2.5 h, 2.6 h, 2.8 h, 3 h, 3.5 h or 4 h.

[0059] In one embodiment, in step (3), except that the second metal salt solution is used to replace the first metal salt solution, other reaction conditions are the same as those in step (2).

[0060] In a second aspect, the present invention provides a sodium-based positive electrode material with a core-shell structure, wherein the sodium-based positive electrode material with a core-shell structure is prepared using the sodium-based positive electrode material precursor with a core-shell structure described in the first aspect, wherein the sodium-based positive electrode material with a core-shell structure comprises a core, a first coating layer, and a second coating layer arranged in sequence from the inside to the outside, wherein the core is a porous structure.

[0061] Preferably, the chemical composition of the core-shell structured sodium positive electrode material is: NaNi x A y B z O2, A includes at least two of Ni, Fe and Mn, B includes at least one of Mn, Cu, Ti and Zr, 0 <x<1,0<y<1,0<z<1。

[0062] The sodium-based positive electrode material of the present invention not only has high capacity and good cycle stability, but also has low preparation cost.

[0063] The present invention does not limit the preparation method of the core-shell structured sodium positive electrode material, and those skilled in the art can refer to the method disclosed in the prior art for preparation. By way of example and not limitation, the preparation method of the core-shell structured sodium positive electrode material comprises the following steps:

[0064] The core-shell structured sodium positive electrode material precursor described in the first aspect is mixed with a sodium source and then sintered to obtain the core-shell structured sodium positive electrode material.

[0065] Preferably, the sodium source includes but is not limited to at least one of sodium carbonate and sodium hydroxide.

[0066] Preferably, the usage amounts of the sodium cathode material precursor and the sodium source satisfy: Na:M=1:1-2, for example, it can be 1:1.01, 1:1.02, 1:1.03, 1:1.05, 1:1.06, 1:1.08, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.7, 1:1.75, 1:1.8, 1:1.85, 1:1.9 or 1:2, etc.

[0067] Wherein, M is the metal element in the precursor of the sodium cathode material.

[0068] Preferably, the sintering atmosphere is an air atmosphere.

[0069] Preferably, the sintering temperature is 600-800°C, for example, it may be 600°C, 650°C, 700°C, 725°C, 750°C, 760°C, 780°C or 800°C.

[0070] Preferably, the sintering time is 6-15 h, for example, it can be 6 h, 6.5 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h.

[0071] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium positive electrode material with a core-shell structure as described in the second aspect.

[0072] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0073] Compared with the prior art, the present invention has the following beneficial effects:

[0074] (1) The precursor of the present invention uses a Ni-based MOF material with a porous structure as the core. The nickel-rich and porous properties can provide a higher capacity for the positive electrode material on the one hand, and on the other hand, it can be more conducive to the entry of sodium ions when preparing the positive electrode material, which is beneficial to improving the power performance of the positive electrode material; the middle layer not only has a lower preparation cost, but also can provide a certain capacity for the positive electrode material prepared by using it; the outer shell layer can effectively improve the structural stability of the positive electrode material prepared by using it.

[0075] (2) The method of the present invention is simple, simplifies the production process of core-shell structure materials, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 This is a scanned image of the core-shell structured sodium cathode material precursor provided in Example 1. DETAILED DESCRIPTION

[0077] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0078] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0079] Example 1

[0080] The present embodiment provides a sodium-based cathode material precursor with a core-shell structure, the sodium-based cathode material precursor with a core-shell structure comprising an inner core, the surface of the inner core is coated with an intermediate layer, the surface of the intermediate layer is coated with an outer shell layer, the inner core is a Ni-based MOF material with a doping element, the Ni-based MOF material with a doping element is Zr-doped ZIF-8, the intermediate layer comprises Ni, Fe and Mn, and the outer shell layer comprises Mn;

[0081] Taking the total mass of the core-shell structured sodium positive electrode material precursor as 100%, the content of the core is 33.34%, the content of the middle layer is 33.33%, and the content of the outer shell layer is 33.33%;

[0082] Based on the total mass of the core-shell structured sodium-based cathode material precursor, the doping amount of Zr is 1000 ppm.

[0083] This embodiment also provides a method for preparing the core-shell structured sodium cathode material precursor, comprising the following steps:

[0084] (1) dissolving 2-methylimidazole in NH4OH solution to obtain solution A; wherein the content of NH3 in the NH4OH solution is 30%, and the concentration of 2-methylimidazole in solution A is 2.0 mol / L;

[0085] Dissolving nickel nitrate and zirconium nitrate in ultrapure water to obtain solution B; wherein the concentration of nickel nitrate in solution B is 1.0 mol / L, and the concentration of zirconium nitrate is 0.1 mol / L;

[0086] At a temperature of 25°C and under stirring conditions, solution A was added to solution B to react for 24 hours, and the solid-liquid separation was performed. The solid was washed with ultrapure water, dried, and ground to obtain Zr-doped ZIF-8.

[0087] (2) using the Zr-doped ZIF-8 described in step (1) to prepare a base solution, wherein the temperature of the base solution is 50° C., the concentration of ammonia water in the base solution is 3 g / L, the concentration of Zr-doped ZIF-8 is 5 g / L, and the pH is 10;

[0088] A nickel-iron-manganese mixed salt solution with a concentration of 100 g / L, a liquid alkali solution with a mass concentration of 20%, and an ammonia solution with a mass concentration of 15% are simultaneously and concurrently added to a reactor containing a bottom liquid at feed rates of 10 L / h, 5 L / h, and 0.5 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 200 r / min. During the reaction, the pH of the reaction system is controlled to be 9-11, the ammonia concentration is 2-4 g / L, and the temperature is 50°C. The particle size is continuously monitored. Before the particle size meets the requirements, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particle size D50 reaches 10 μm, the feeding is stopped, and the nickel-iron-manganese mixed salt solution is replaced with a 100 g / L manganese sulfate solution. The flow rates of other auxiliary materials remain unchanged, and the feeding is continued for 3 hours. Then the reaction is stopped to obtain a sodium cathode material precursor with a core-shell structure.

[0089] This embodiment also provides a core-shell structured sodium battery positive electrode material prepared by using the core-shell structured sodium battery positive electrode material precursor, and the preparation method thereof comprises the following steps:

[0090] 2000g of the precursor and Na2CO3 were mixed evenly in a high-speed mixer at a molar ratio of Na:M (wherein M is the metal element in the precursor) = 1:1.05, and sintered in a box furnace under an air atmosphere at a sintering temperature of 700°C for 10 hours. After cooling to room temperature, the mixture was crushed and sieved to obtain a sodium positive electrode material with a core-shell structure.

[0091] Figure 1 This is a scan of the core-shell structured sodium cathode material precursor provided in Example 1. It can be seen from the figure that the prepared precursor has good dispersibility, good sphericity, uniform primary particles, and no phase separation.

[0092] Example 2

[0093] The present embodiment provides a sodium-based cathode material precursor with a core-shell structure, the sodium-based cathode material precursor with a core-shell structure comprising an inner core, the surface of the inner core is coated with an intermediate layer, the surface of the intermediate layer is coated with an outer shell layer, the inner core is a Ni-based MOF material with a doping element, the Ni-based MOF material with a doping element is Zr-doped ZIF-8, the intermediate layer comprises at least two of Ni, Fe and Mn, and the outer shell layer comprises at least one of Mn, Cu, Ti and Zr;

[0094] Taking the total mass of the core-shell structured sodium positive electrode material precursor as 100%, the content of the core is 33.34%, the content of the middle layer is 40.00%, and the content of the outer shell layer is 26.66%;

[0095] Based on the total mass of the core-shell structured sodium-based cathode material precursor, the doping amount of Zr is 1000 ppm.

[0096] This embodiment also provides a method for preparing the core-shell structured sodium cathode material precursor, comprising the following steps:

[0097] (1) dissolving 2-methylimidazole in NH4OH solution to obtain solution A; wherein the content of NH3 in the NH4OH solution is 40%, and the concentration of 2-methylimidazole in solution A is 3.5 mol / L;

[0098] Dissolving nickel nitrate and zirconium nitrate in ultrapure water to obtain solution B; wherein the concentration of nickel nitrate in solution B is 1.2 mol / L, and the concentration of zirconium nitrate is 0.14 mol / L;

[0099] At a temperature of 30°C and under stirring conditions, solution A was added to solution B for reaction for 30 hours, and the solid-liquid separation was performed. The solid was washed with ultrapure water, dried and ground to obtain Zr-doped ZIF-8.

[0100] (2) using the Zr-doped ZIF-8 described in step (1) to prepare a base solution, wherein the temperature of the base solution is 70° C., the concentration of ammonia water in the base solution is 10 g / L, the concentration of Zr-doped ZIF-8 is 8 g / L, and the pH is 12;

[0101] A nickel-iron-manganese mixed salt solution with a concentration of 120 g / L, a liquid alkali solution with a mass concentration of 10%, and an ammonia solution with a mass concentration of 20% are simultaneously and concurrently added to a reactor containing a bottom liquid at feed rates of 3 L / h, 7 L / h, and 1 L / h, respectively, and a coprecipitation reaction is carried out at a stirring rate of 400 r / min. During the reaction, the pH of the reaction system is controlled to be 11-12.5, the ammonia concentration is 9-11 g / L, and the temperature is 70°C. The particle size is continuously monitored. Before the particle size meets the requirements, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particle size D50 reaches 12 μm, the feeding is stopped, and the nickel-iron-manganese mixed salt solution is replaced with a 120 g / L manganese sulfate solution. The flow rates of other auxiliary materials remain unchanged, and the feeding is continued for 4 hours. Then the reaction is stopped to obtain a sodium cathode material precursor with a core-shell structure.

[0102] This embodiment also provides a core-shell structured sodium battery positive electrode material prepared by using the core-shell structured sodium battery positive electrode material precursor, and the preparation method thereof comprises the following steps:

[0103] 2000g of the precursor and Na2CO3 were mixed evenly in a high-speed mixer at a molar ratio of Na:M (wherein M is the metal element in the precursor) = 1:1.1, and sintered in a box furnace under an air atmosphere at a sintering temperature of 600°C for 15 hours. After cooling to room temperature, the mixture was crushed and sieved to obtain a sodium positive electrode material with a core-shell structure.

[0104] Example 3

[0105] The present embodiment provides a sodium-based cathode material precursor with a core-shell structure, the sodium-based cathode material precursor with a core-shell structure comprising an inner core, a surface of the inner core being coated with an intermediate layer, a surface of the intermediate layer being coated with an outer shell layer, the inner core being a Ni-based MOF material with a doping element, the Ni-based MOF material with a doping element being Zr-doped ZIF-8, the intermediate layer comprising Fe and Mn, and the outer shell comprising Cu;

[0106] Taking the total mass of the core-shell structured sodium positive electrode material precursor as 100%, the content of the core is 33.34%, the content of the middle layer is 50.00%, and the content of the outer shell layer is 16.66%;

[0107] Based on the total mass of the core-shell structured sodium-based cathode material precursor, the doping amount of Zr is 1000 ppm.

[0108] This embodiment also provides a method for preparing the core-shell structured sodium cathode material precursor, comprising the following steps:

[0109] (1) dissolving 2-methylimidazole in NH4OH solution to obtain solution A; wherein the content of NH3 in the NH4OH solution is 25%, and the concentration of 2-methylimidazole in solution A is 3.0 mol / L;

[0110] Dissolving nickel nitrate and zirconium nitrate in ultrapure water to obtain solution B; wherein the concentration of nickel nitrate in solution B is 0.6 mol / L, and the concentration of zirconium nitrate is 0.07 mol / L;

[0111] At a temperature of 25°C and under stirring conditions, solution A was added to solution B to react for 20 hours, and the solid-liquid was separated. The solid was washed with ultrapure water, dried and ground to obtain Zr-doped ZIF-8.

[0112] (2) using the Zr-doped ZIF-8 described in step (1) to prepare a base solution, wherein the temperature of the base solution is 35° C., the concentration of ammonia water in the base solution is 0.1 g / L, the concentration of Zr-doped ZIF-8 is 2 g / L, and the pH is 7.5;

[0113] An iron-manganese mixed salt solution with a concentration of 80 g / L, a liquid alkali solution with a mass concentration of 20%, and an ammonia solution with a mass concentration of 15% are simultaneously and concurrently added to a reactor containing a base liquid at feed rates of 5 L / h, 2 L / h, and 0.3 L / h, respectively, and a co-precipitation reaction is carried out at a stirring rate of 100 r / min. During the reaction, the pH of the reaction system is controlled to be 8-9, the ammonia concentration is 1-2 g / L, and the temperature is 60°C. The particle size is continuously monitored. Before the particle size meets the requirements, a high-efficiency concentrator is used in the reaction process to collect all the particles and return them to the reactor for continuous reaction and growth. When the particle size D50 reaches 11 μm, the feeding is stopped, and the iron-manganese mixed salt solution is replaced with an 80 g / L copper sulfate solution. The flow rates of other auxiliary materials remain unchanged, and the feeding is continued for 4 hours. Then the reaction is stopped to obtain a core-shell structured sodium cathode material precursor.

[0114] This embodiment also provides a core-shell structured sodium battery positive electrode material prepared by using the core-shell structured sodium battery positive electrode material precursor, and the preparation method thereof comprises the following steps:

[0115] 2000g of the precursor and Na2CO3 were mixed evenly in a high-speed mixer at a molar ratio of Na:M (wherein M is the metal element in the precursor) = 1:1.08, and sintered in a box furnace under an air atmosphere at a sintering temperature of 800°C for 6 hours. After cooling to room temperature, the mixture was crushed and sieved to obtain a sodium positive electrode material with a core-shell structure.

[0116] The composition of the core-shell structure sodium positive electrode material prepared in this embodiment is NaNi0.333Fe0.333Mn0.333Zr0.001O2.

[0117] Example 4

[0118] The difference between this embodiment and embodiment 1 is that, based on the total mass of the core-shell structured sodium cathode material precursor, the doping amount of Zr is 200 ppm.

[0119] Example 5

[0120] The difference between this embodiment and embodiment 1 is that, based on the total mass of the core-shell structured sodium cathode material precursor, the doping amount of Zr is 3000 ppm.

[0121] Example 6

[0122] The difference between this embodiment and embodiment 1 is that in the method for preparing the precursor, the time for continuing to feed after replacing the nickel-iron-manganese mixed salt solution with a manganese sulfate solution in step (2) is changed from 3 hours in embodiment 1 to 0.5 hours.

[0123] Example 7

[0124] The difference between this embodiment and embodiment 1 is that in the method for preparing the precursor, the time for continuing to feed after replacing the nickel-iron-manganese mixed salt solution with a manganese sulfate solution in step (2) is changed from 3 hours in embodiment 1 to 6 hours.

[0125] Comparative Example 1

[0126] The difference between this embodiment and embodiment 1 is that in the preparation method of the precursor, Zr-doped ZIF-8 is not prepared, and the base liquid does not contain Zr-doped ZIF-8.

[0127] Comparative Example 2

[0128] The difference between this embodiment and embodiment 1 is that in the method for preparing the precursor, the nickel-iron-manganese salt solution is not replaced by a manganese sulfate solution, but the nickel-iron-manganese salt solution is still used to continue feeding.

[0129] Battery Assembly:

[0130] The positive electrode materials prepared in various embodiments and comparative examples were prepared into positive electrode sheets, wherein the mass ratio of the positive electrode material to the conductive agent Super P and the binder PVDF was 95:2:3.

[0131] A sodium ion battery is prepared by combining a positive electrode plate with a sodium plate, a polyethylene separator and an electrolyte (the electrolyte being sodium hexafluorophosphate).

[0132] Performance test of sodium ion battery:

[0133] The test conditions are to cycle at 25°C with a charge and discharge rate of 0.5C. After 100 cycles, the discharge capacity of the battery at this time is divided by the discharge capacity of the first cycle, which is the battery's 100-cycle capacity retention rate.

[0134] The results are shown in Table 1.

[0135] Table 1

[0136]

[0137]

[0138] As can be seen from Table 1, the precursor of the present invention uses a Ni-based MOF material with a porous structure as the core. The nickel-rich and porous properties make the prepared sodium battery positive electrode material have high capacity and good cycle stability, and its preparation cost is low.

[0139] At the same time, by comparing Example 1 with Examples 4-5, it can be seen that there is a preferred range for the Zr doping amount in step (2), and too small or too large a doping amount will lead to a decrease in the first discharge capacity and cycle performance.

[0140] At the same time, by comparing Example 1 with Examples 6-7, it can be seen that by adjusting the time for continuing to feed after replacing the nickel-iron-manganese mixed salt solution with the manganese sulfate solution, the content of the shell can be adjusted. This time has a preferred range. Too short or too long will lead to a decrease in the first discharge capacity and cycle performance.

[0141] By comparing Example 1 with Comparative Example 1, it can be seen that if Zr-doped ZIF-8 is not added to the base solution, the electrochemical performance will be greatly reduced.

[0142] By comparing Example 1 with Comparative Example 2, it can be seen that if no outer shell is prepared but only the middle layer material is thickened, the synergistic effect of the middle layer and the outer shell layer will be lost, resulting in a significant decrease in electrochemical performance.

[0143] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A core-shell structured sodium cathode material precursor, characterized in that: The core-shell structured sodium positive electrode material precursor comprises an inner core, the surface of the inner core is coated with an intermediate layer, the surface of the intermediate layer is coated with an outer shell layer, the inner core is a Ni-based MOF material with doping elements, the intermediate layer comprises at least two of Ni, Fe and Mn, and the outer shell layer comprises at least one of Mn, Cu, Ti and Zr.

2. The core-shell structured sodium cathode material precursor according to claim 1, characterized in that: The doping element includes at least one of Cu, Al, Mg, Zr, Ti and Ca; Preferably, based on the total mass of the core-shell structured sodium cathode material precursor, the doping amount of the doping element is 800-2500 ppm; Preferably, based on the total mass of the core-shell structured sodium cathode material precursor as 100%, the content of the core is 10-40%; Preferably, based on the total mass of the core-shell structured sodium cathode material precursor being 100%, the content of the intermediate layer is 20-80%; Preferably, based on the total mass of the core-shell structured sodium cathode material precursor being 100%, the content of the outer shell layer is 10-40%.

3. A method for preparing a core-shell structured sodium cathode material precursor as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) providing a Ni-based MOF material having a doping element, and preparing a base liquid using the Ni-based MOF material having a doping element; (2) adding a first metal salt solution, a precipitant solution and a complexing agent solution to the base solution in parallel to perform a coprecipitation reaction, wherein the metal element in the first metal salt solution is of the same type as the metal element in the intermediate layer, thereby obtaining an inner core coated with the intermediate layer; (3) replacing the first metal salt solution with a second metal salt solution, wherein the metal element in the second metal salt solution is consistent with the type of the metal element in the outer shell layer, and continuing the coprecipitation reaction to obtain the core-shell structured sodium cathode material precursor.

4. The preparation method according to claim 3, characterized in that: The method for preparing the Ni-based MOF material with doping elements in step (1) comprises: (a) mixing a reaction substrate, a catalyst and a solvent to obtain a solution A; (b) dissolving nickel salt and M salt in a solvent, where M is a doping element, to obtain solution B; (c) Solution A and solution B are mixed and reacted to obtain a Ni-based MOF material with doping elements.

5. The preparation method according to claim 4, characterized in that: In step (a), the reaction matrix includes at least one of 2-methylimidazole, benzimidazole and bisbenzimidazole; Preferably, the catalyst is selected from at least one of NH4OH and NaOH, preferably NH4OH; Preferably, step (a) is: dissolving the reaction substrate in NH4OH solution to obtain solution A; Preferably, the mass content of NH3 in the NH4OH solution is 25-40%; Preferably, in step (a), the concentration of 2-methylimidazole in the solution A is 1.9-3.8 mol / L; Preferably, the nickel salt in step (b) is at least one of nitrate, sulfate or chloride; Preferably, the M salt in step (b) is at least one of nitrate, sulfate or chloride; Preferably, in step (b), the concentration of the nickel salt in the solution B is 0.6-1.2 mol / L; Preferably, in step (b), the concentration of the M salt in the solution B is 0.07-0.14 mol / L; Preferably, in step (c), the mixing and reacting process is carried out under stirring conditions; Preferably, in step (c), the temperature of the mixing and reaction is 20-30°C; Preferably, in step (c), the reaction time is 20-30h; Preferably, in step (c), after the reaction, the steps of solid-liquid separation, solid washing, drying and grinding are further performed.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the concentration of the Ni-based MOF material with doping elements in the base solution is 2-8 g / L; Preferably, in step (1), the temperature of the base liquid is 20-80°C; Preferably, in step (1), the concentration of aqueous ammonia in the base solution is 0-10 g / L; Preferably, in step (1), the pH of the base solution is 8-12.

7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (2) The concentration of the first metal salt solution is 80-120 g / L; Preferably, the feeding rate of the first metal salt solution in step (2) is 1-10 L / h; Preferably, the mass concentration of the precipitant solution in step (2) is 10-30%; Preferably, the feed rate of the precipitant solution in step (2) is 1-7 L / h; Preferably, the mass concentration of the complexing agent solution in step (2) is 10-20%; Preferably, the feeding rate of the complexing agent solution in step (2) is 0.1-1 L / h; Preferably, the temperature of the coprecipitation reaction in step (2) is 20-80°C; Preferably, the coprecipitation reaction in step (2) is accompanied by stirring at a speed of 100-400 r / min; Preferably, the ammonia concentration in the coprecipitation reaction system in step (2) is 0-13 g / L; Preferably, in step (2), the pH of the coprecipitation reaction is 8-12.5; Preferably, the particle size D50 of the inner core coated by the intermediate layer in step (2) is 10-12 μm.

8. The preparation method according to any one of claims 4 to 7, characterized in that: Step (3) the concentration of the second metal salt solution is 80-120 g / L; Preferably, the feeding rate of the second metal salt solution in step (3) is 1-10 L / h; Preferably, the second metal salt in the second metal salt solution in step (3) is sulfate; Preferably, the coprecipitation reaction in step (3) is continued for 2-4 hours.

9. A sodium cathode material with a core-shell structure, characterized in that: The core-shell structured sodium positive electrode material is prepared by using the core-shell structured sodium positive electrode material precursor according to any one of claims 1 to 3, wherein the core-shell structured sodium positive electrode material precursor comprises a core, a first coating layer and a second coating layer arranged in sequence from the inside to the outside, and the core is a porous structure; Preferably, the chemical composition of the core-shell structured sodium positive electrode material is: NaNi x A y B z O2, A includes at least two of Ni, Fe and Mn, B includes at least one of Mn, Cu, Ti and Zr, 0 <x<1,0<y<1,0<z<1。 10. A sodium ion battery, characterized in that: The sodium ion battery comprises the core-shell structured sodium positive electrode material according to claim 9.